UVB irradiation on human dermal fibroblasts - Liu, L (2023)
UVB is a primary contributor to extrinsic skin aging, and a comprehensive understanding of its impact on human skin is crucial for elucidating the aging process and facilitating the development of effective drug treatments. Additionally, UVB plays a pivotal role in vitamin D synthesis within dermal fibroblasts, underscoring its positive effects on dermal health. Therefore, an in-depth investigation into the influence of UVB irradiation on dermal fibroblasts is not only essential for advancing our understanding of skin aging but also serves as a foundational aspect of this thesis, bridging the gap between detrimental and beneficial effects of UVB in skin research. This study examines the effects of UVB irradiation on human primary dermal fibroblasts from PromoCell, mostly based on comprehensive full factorial experiments, focusing on cell proliferation, migration, ROS changes, and levels of collagen type I and MMP1. The underlying mechanisms were further explored using mRNA analysis and assay of cell senescence and cycle dynamics. The findings of our research highlight the significance of the UVB irradiation medium, demonstrating that Fibroblast Basal Medium (FBM) effectively reduces UVB-induced damage, increasing cell number as the same level as the non UVB irradiated groups. This is observed through the interplay among UVB rays, dermal fibroblasts, and the irradiation medium. The protective effect of FBM is most evident under conditions of 10,000 cells/cm2 seeding density and minimal UVB exposure of 40 mJ/cm2. Additionally, the incorporation of the molecular component RE (mixture of FBM and cell secretome)is pivotal in counteracting the detrimental effects of UVB. RE not only overcomes limitations related to cell density but also promotes enhanced cell growth, surpassing even the growth rates of the control group without UVB exposure, up to 134% under tested conditions , by influencing cell cycle progression. The mitigating impact of this approach is significantly noticeable in aspects such as cell proliferation, collagen type I protein levels, cell cycle dynamics, and pathway enrichment. However, the effects are less pronounced in cell migration and show variable results in MMP1 protein levels. This research advances our understanding of UVB effects on dermal fibroblasts, highlighting the protective role of irradidation media: FBM and RE. These findings contribute significantly to skin aging research and offer potential for new treatments, providing a foundation for future dermatological innovations and enhancing the current knowledge base in the field.